PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP KEMAMPUAN PRAKTIK KEWIRAUSAHAAN MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU DARI TAHUN 2019-2021 - Rosmiati Rosmiati; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out whether entrepreneurial knowledge influences the ability to practice entrepreneurship in Economics Education FKIP University of Riau students from 2019-2021. While collecting data in this study by means of random sampling. Where random sampling is a sampling technique or random elements where each element or member of the population has the same opportunity to be sampled. The type of data used is secondary data, namely the results of the semester final exam scores for the subject of entrepreneurship knowledge and entrepreneurial practices of Economics Education students at the Faculty of Teacher Training and Education, University of Riau. The statistical method used to test the research hypothesis is simple linear regression with the help of the Statistical Package for Social Science (SPSS) program. Based on the results of this study, it shows that: entrepreneurial knowledge influences the ability to practice entrepreneurship in Economics education students class of 2019-2021. Based on the results of this study it can be recommended; 1) It is hoped that the results of this research can provide information in making the right decisions, research can be used as material for consideration in banning the course. 2) For Economics Education Students, this research can be used as reading material to provide knowledge, attitudes and skills to students so that they become students who have a strong entrepreneurial spirit and achieve students in the appeal of entrepreneurship science. 3) For future researchers, the results of this study are expected to be a reference or reference for conducting further research and used in solving the same problem as this research.Key Words: The Effect of Knowledge, Ability to Practice Entrepreneurship